Asian labor in the wartime Japanese empire : unknown histories - Kratoska, Paul H. (An East Gate book., 2005)
During the Pacific War the Japanese government used a wide range of methods to recruit workers for construction projects throughout the occupied territories. Mistreatment of workers was a major grievance, both in widely publicized cases such as the use of prisoners of war and forced Asian labor to construct the Thailand-Burma ""Death"" Railway, and in a very large number of smaller projects. In this book an international group of specialists on the Occupation period examine the labor needs and the recruitment and use of workers (whether forced, military, or otherwise) throughout the Japanese e